Studi Dinamika Molekul Stabilisasi Metaloproteinase Matriks 9 oleh Asam Kafeat: Molecular Dynamics Studies of Matrix Metalloprotenase-9 Stabilization by Caffeic Acid - Istyastono, Enade Perdana (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
Caffeic acid, a cathecol-containing phytochemical found in coffee, has been reported as a potent matrix metalloproteinase 9 (MMP9) inhibitor. The IC50 value of caffeic acid as MMP9 inhibitor could reach below 20 nM. The research presented in this article employed molecular dynamics simulations to unravel the atomic mechanism of the MMP9 inhibition by caffeic acid. Molecular dynamics simulations of MMP9 for 10 ns using YASARA-Structure were performed with and without caffeic acid as the studied ligand. The results showed that caffeic acid stabilized the stucture of the MMP9.